MR1, an immunological periscope of cellular metabolism. (27th October 2021) - Chancellor, Andrew; Vacchini, Alessandro; De Libero, Gennaro
Abstract: The discovery that major histocompatibility complex (MHC) class I-related molecule 1 (MR1) presents microbial antigens to mucosal-associated invariant T (MAIT) cells was a significant scientific milestone in the last decade. Surveillance for foreign metabolically derived antigens added a new class of target structures for immune recognition. The recent identification of a second family of MR1-restricted T cells, called MR1T cells, which show self-reactivity suggests the microbial antigens characterized so far may only represent a handful of the potential structures presented by MR1. Furthermore, the reactivity of MR1T cells towards tumours and not healthy cells indicates tight regulation in the generation of self-antigens and in MR1 expression and antigen loading. These novel and exciting observations invite consideration of new perspectives of MR1-restricted antigen presentation and its wider role within immunity and disease. Abstract : MR1-retricted T cells in health and disease Graphical Abstract: